P/Q‐type and T‐type voltage‐gated calcium channels are involved in the contraction of mammary and brain blood vessels from hypertensive patients. (29th June 2016) - Thuesen, A. D.; Lyngsø, K. S.; Rasmussen, L.; Stubbe, J.; Skøtt, O.; Poulsen, F. R.; Pedersen, C. B.; Rasmussen, L. M.; Hansen, P. B. L.
Abstract: Aim: Calcium channel blockers are widely used in cardiovascular diseases. Besides L‐type channels, T‐ and P/Q‐type calcium channels are involved in the contraction of human renal blood vessels. It was hypothesized that T‐ and P/Q‐type channels are involved in the contraction of human brain and mammary blood vessels. Methods: Internal mammary arteries from bypass surgery patients and cerebral arterioles from patients with brain tumours with and without hypertension were tested in a myograph and perfusion set‐up. PCR and immunohistochemistry were performed on isolated blood vessels. Results: The P/Q‐type antagonist ω‐agatoxin IVA (10 −8  mol L −1 ) and the T‐type calcium blocker mibefradil (10 −7  mol L −1 ) inhibited KCl depolarization‐induced contraction in mammary arteries from hypertensive patients with no effect on blood vessels from normotensive patients. ω‐Agatoxin IVA decreased contraction in cerebral arterioles from hypertensive patients. L‐type blocker nifedipine abolished the contraction in mammary arteries. PCR analysis showed expression of P/Q‐type (Cav 2.1), T‐type (Cav 3.1 and Cav 3.2) and L‐type (Cav 1.2) calcium channels in mammary and cerebral arteries. Immunohistochemical labelling of mammary and cerebral arteries revealed the presence of Cav 2.1 in endothelial and smooth muscle cells. Cav 3.1 was also detected in mammary arteries. Conclusion: P/Q‐ and T‐type Cav are present in human internal mammary arteries and in cerebral penetrating arterioles. P/Q‐ and T‐type calcium channels are involved in the contraction of mammary arteries from hypertensive patients but not from normotensive patients. Furthermore, in cerebral arterioles P/Q‐type channels importance was restricted to hypertensive patients might lead to that T‐ and P/Q‐type channels could be a new target in hypertensive patients.